Perception of Open Access by teacher-researchers at Marien Ngouabi University - (:unkn) unknown (My University, 2023)
Open Access or free access concerns the world of scientific research and means giving free access to scientific publications online with-out any legal, technical or financial barrier. This ideology, born in 90, is motivated by the need to overcome the lack of ressources of researchers by facilitating their access to research results through non-profits platforms. This provides more visibility for publications, but also assumes that researchers do not receive any compensation for work they publish on these platforms. Open Access has indeed spread all over the world to Africa. How-ever, the concept of Open Access has only very recently been installed in the African scientific environment, even if significant advances have been made here and there. It is therefore still fairly new concept for most researchers in certain regions of the continent, particulary in French-speaking sub-Saharan Africa and Congo Brazzaville in particular. The purpose of this study is to know what the teacher-researchers of Marien Ngouabi University think of the Open Access movement to try to understand how it can be applied in the best possible way at the local area.
Keywords: African Research